Bioenergetic Habitat Suitability Curves for Instream Flow Modeling: Introducing User‐Friendly Software and its Potential Applications. Issue 11 (8th September 2020) - Naman, Sean M.; Rosenfeld, Jordan S.; Neuswanger, Jason R.; Enders, Eva C.; Hayes, John W.; Goodwin, Eric O.; Jowett, Ian.G.; Eaton, Brett C.
Abstract : Habitat suitability curves (HSCs) are the biological component of habitat simulation tools used to evaluate instream flow management trade‐offs (e.g., the physical habitat simulation model). However, traditional HSCs based on empirical observations of habitat use relative to availability have been criticized for generating biased estimates of flow requirements and for being poorly transferable across locations. For fish like salmonids that feed on drifting invertebrates, bioenergetics‐based foraging models that relate habitat conditions to net energy gain offer an alternative approach that addresses some of these shortcomings. To make this technique more accessible for practitioners, we present free and user‐friendly software for generating bioenergetics‐based HSCs. The software also allows sensitivity analyses of HSCs to factors like fish size or prey abundance as well as direct integration of hydraulic data. While some caveats remain, bioenergetic HSCs should offer a more rigorous and credible means for quantifying habitat suitability for instream flow modeling.